Learning instructional using webbed models based on local potential "Pulau Kembang" to enhance ecological literacy skill - Desy Purwasih; Insih Wilujeng; Vietgar Membalik; Suhandi Hasan (Jurnal Inovasi Pendidikan IPA, 2022)
The research is developing a webbed integrated science learning model based on the local potential "Pulau Kembang" discovery learning (DL) model to improve ecological literacy skills. The purpose of this research is to produce a product that is feasible, practical, and effective for use in learning. The type of research is educational research design by adapting the Borg Gall development model, consisting of ten stages. Media experts, material experts, and practitioners conducted the feasibility assessment, totaling five people. The effectiveness was obtained from a limited trial with a pretest experimental design and a posttest control group design. There is one control class and one practical class with 49 students. The effectiveness analysis used the Analysis of Variance (ANOVA). The product practicality test provides a response questionnaire with a 4-Likert scale, totaling 27 statements. The results show that the average lesson plan is 1.00 in the excellent category, the student worksheets are on average 3.56 in the excellent category, the handout is on average 3.44 in the excellent category, and the assessment instrument with a V-Aiken value of 1.00 is in an excellent category. The results of the ANOVA test get a p-value 0.005 and an effect size of 0.171 in the large category. Practicality test with an average of 3.08 suitable type. Overall, it shows that the webbed integrated model of science learning instructional based on local potential "Pulau Kembang" is feasible and practical to use in learning.